Implementasi Teknologi Genetika Untuk Konservasi Spesies Laut Terancam: Tinjauan Literatur Tentang Metode dan Keberhasilan - Betzy Victor Telaumbanua; Destriman Laoli; Ratna Dewi Zebua; Okniel Zebua; Januari Dawolo; Asokhiwa Zega (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
The pace of global environmental change and the intensification of human activities have put significant pressure on marine ecosystems, threatening the sustainability of many species that are important both for ecosystems and the economies of coastal communities. In this context, this study aims to evaluate the application of genetic technologies in the conservation of endangered marine species, focusing on environmental DNA (eDNA) monitoring, CRISPR genetic engineering techniques and population genetic analysis. The method used was a literature review that examined current academic sources related to genetic technologies and their implementation in conservation. Findings show that eDNA is a highly effective tool in species and habitat monitoring, and has been successful in specific cases such as Napoleon fish and green turtles in Raja Ampat. In contrast, CRISPR techniques offer the potential to improve the genetic resilience of species, despite significant regulatory and ethical challenges. The implications of this study emphasize the need for strong policy support and international collaboration to address these challenges and optimize the use of genetic technologies in more effective conservation strategies in the future.